PENGARUH CLICKBAIT JOURNALISM TERHADAP MINAT BACA GENERASI Z - Nurisma Rahmatika; Syahrul Hidayanto (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
Attention economy makes online journalism work with the principle of prioritizing high clickers and viewers. To achieve this goal, journalists apply the clickbait strategy to their journalistic products. This strategy impacts the quality of online news. Nevertheless, clickbait news is still accessed by the public, especially generation Z. This research was conducted to determine the effect of clickbait journalism on the reading interest of generation Z. The method used is a positivist paradigm with a quantitative approach. Data were collected using a questionnaire. The data source was selected using a purposive sampling technique with the criteria of respondents being the Z generation who live in Jakarta and have read online news. The results of this study indicate that clickbait journalism has a positive and significant effect on interest in reading generation Z. This finding proves that Loewenstein's information gap theory applies in this study.